LA CONSTITUCIÓN DE RIONEGRO ANTECEDENTES Y ESFUERZOS EN LA CONCRECIÓN DE UN SISTEMA POLÍTICO PARA COLOMBIA (2016)
In this article, we refer to the history of the Charter of Rionegro and their contribution to setting up a political system to Colombia, in particular its contribution to the significant share of power in the territory of the former New Granada generated by it. The text includes shallow way, and just as similar background, the general characteristics of territorial political organization of the Chibcha Civilization and the political and administrative structure of the state in colonial times. However, before addressing the matter under review, it is necessary to address two important issues: a forced, which provides the conceptual framework for the development of the text, and the other referring both to the outstanding figures of the constituents eponymous 1863 as for democratic institutions more advanced in that Constitution.The Constitution of Rionegro, federal extreme, the most of their gender and, therefore, also considered as the most democratic progress throughout our constitutional history, however, was disqualified by Victor Hugo, French poet, as “ constitution for angels, “but we think only in terms of the collated with materials difficult political circumstances and lived in their country at the end of his life, referring to excessive centralization Europe, particularly with French unitary authoritarian regime in force in the anti-democratic interregnum elapsed between the second and third republics, suffered by him, and abruptly imposed by Emperor Louis Napoleon, whom Marx wrote the 18 Brumaire.